(untitled) (American Journal of Islam and Society, 1993)
This book is based mainly on an earlier small book entitled Race and Color in Islam that was published in 1971. In this new edition, Lewis added more chapters and expanded the discussion of some of the material that he examined in the earlier edition. He mentions that scholarly work on the topic of slavery received only limited attention from researchers compared with studies on slavery in the Greek and Roman worlds. Only a few number of studies of high caliber could be cited. The main theme of the book, as Lewis states clearly in his concluding remarks, is that Islam’s total racial hannony and ilUlocence is a myth created, maintained, and idealized by westerners as a rebuke to the actions of the white man in the Americas and South Africa. Moreover, the idea found relevance among missionaries in Africa who tried to seek explanations for their failure in contrast to the success of Islam. In his analysis, Lewis tries lo distinguish between three distinct meanings of Islam: 1) Islam as the religion taught by the Prophet and prescribed in the Qur’an; 2) Islam as a larger body including the traditions, works, and fatwas of Islamic scholars and jurists. In this regard Islam includes the Shari’ah as developed over the centuries; and 3) Islam as the counterpart not of Christianity but of Christendom. Here, Islam means not ...